KEUNTUNGAN USAHATANI PADI (Oryza sativa L) DI DESA KELADAN BARU KECAMATAN GAMBUT KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Wasdiyanta Wasdiyanta (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
Research aims to know paddy farming management is sighted from technical aspect, know how big, acceptance and gain of Silvan paddy farming At Keladan Baru Village On this research meode which is utilized is with method surveys with observation tech, panarikan samples to utilize simple random tech( Simple random is sampling.  Its outgrows total farmer that labour varietas's paddy farming Unus's Siam local as much 118 person, take at random simple( Simple Random is Sampling ) as much 25 % (30 person) of all population Acquired production of paddy farming average 2.679,00 kg / farmer or as big as 4.252,38 kg / ha (4,25 tons / ha) with average 267,90 blek / farmers or as big as 425,24 tin cans / ha. Acceptance on paddy farming average as big as Rp. 24. 111. 000,00 / farmer or Rp. 38. 271. 428,57 / ha. Averagely gain which gotten by farmer in one season plants out is as big as Rp. 19. 994. 267,93 / farmers or on a par as big as Rp. 31. 736. 933,23 / ha.